Pengaruh Desain Produk, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Masker Clay Stick Skintific Pada Platform E-Commerce Shopee Di Bekasi Utara - Istiningrum, Fadya Dwi; Dharmanto, Agus; Wijayanti, Murti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of product design, price, and product quality on the purchase decision of Skintific clay stick masks through the Shopee e-commerce platform in North Bekasi. The research method used is quantitative, with questionnaires distributed to 96 respondents who reside in North Bekasi and have purchased the product. The data were analyzed using SPSS software. The results of the study indicate that all three independent variables have a positive and significant effect on purchase decisions, both partially and simultaneously. These findings highlight the importance for companies to consider aspects of design, price, and quality in their skincare product marketing strategies on digital platforms